Lawsuits in a market economy : the evolution of civil litigation - Yeazell, Stephen C. (Chicago : The University of Chicago Press, 2019)
Some describe civil litigation as little more than a drag on the economy; others hail it as the solution to most of the country's problems Stephen C. Yeazell argues that both positions are wrong. Deeply embedded in our political & economic systems, civil litigation is both a system for resolving disputes & a successful business model, a fact that both its opponents & its fans do their best to conceal. 'Lawsuits in a Market Economy' explains how contemporary civil litigation in the United States works & how it has changed over the past century. The text corrects common misconceptions - some of which have proved remarkably durable even in the face of contrary evidence - & explores how our constitutional structure, an evolving economy, & developments in procedural rules & litigation financing systemss have moved us from expecting that lawsuits end in trial & judgment to expecting that they will end in settlements.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 9, 2019).
Keywords: Class actions (Civil procedure) -- United States; Class actions (Civil procedure) -- Economic aspects -- United States; Class actions (Civil procedure) -- Political aspects -- United States; Civil procedure -- United States; Actions and defenses -- United States; Law; Laws of specific jurisdictions & specific areas of law